Bacterial Communities of Mojave Desert Biological Soil Crusts Are Shaped by Dominant Photoautotrophs and the Presence of Hypolithic Niches - Fisher, Kirsten; Jefferson, Jameka S.; Vaishampayan, Parag (Frontiers in Ecology and Evolution, 2020)
Biocrust communities are often heterogeneous and affected by small-scale physical and environmental factors. The presence of moss in biocrusts, for example, is likely to create a set of physical conditions distinct from those found in biocrusts that lack mosses. Similarly, hypolithic organisms living under and on the belowground surface of translucent and opaque stones (typically quartz) experience a distinct environment relative to surrounding soil surface organisms. To understand the impact of these factors on biocrust bacterial community composition, we performed 16S rRNA sequencing from surface and hypolithic biocrusts with and without the common biocrust moss, Syntrichia caninervis. While alpha diversity indices did not differ significantly between any of the biocrust habitats sampled, we did observe differences in overall community composition. Cyanobacterial abundance and diversity decreased in the presence of moss and in surface samples compared to hypolithic biocrusts, while Proteobacteria showed the opposite pattern. Acidobacteria were significantly more abundant in hypolithic niches, and Patescibacteria were found to be restricted to moss-dominated surface biocrusts. Notably, bacterial community composition was found to shift significantly between surface and hypolithic biocrusts lacking moss (Adonis, R2 = 0.122, p = 0.002) and between surface moss and non-moss biocrusts (R2 = 0.107, p = 0.002). These findings support the idea that even at small spatial scales (e.g., within < 10 cm), desert biocrust bacterial community composition varies based on the habitat structure and cohabitants.